Modifikasi Lanjut Alat Pemipil Jagung Semi Mekanis - GP, Muhammad Wahyudi; Tamrin, Tamrin; Rahmawati, Winda (abe.fp.unila.ac.id, 2023)
Corn sheller is a tool designed to improve the results of shelled corn. Based on previous research tests, several obstacles and weaknesses were found in the tool, namely the large corn cobs were stuck and the lever rotation felt heavy. To overcome this problem, it is necessary to modify the corn sheller. The method in this study included modification of a semi-mechanical corn sheller and experiments on a semi-mechanical corn sheller. Testing the performance of the corn sheller was carried out by calculating the value of the parameters including the working capacity of the machine (kg/hour), the amount of shelled corn (%), and the amount of corn that was not shelled (%) which was tested on a semi-mechanical corn sheller with 3 Repeat and add different amounts of corn. The semi-mechanical corn sheller was successfully modified and a prototype of a semi-mechanical corn sheller with dimensions of 30 cm x 30 cm x 171cm was made, by reducing the sheller gear cylinder to 34.16 inches before modifying it to 73.3 inches and changing the sheller teeth to 4 before being modified. 8 gear modification. The sheller with 4 teeth with input of 2 cobs is the sheller with the most shelled results, namely 94% and only 6% is not shelled. The sheller with 1 corn cob was the sheller with the lowest yield, namely only 71.48% and the sheller with 3 corn cobs was 77.40%. The highest work capacity in this semi-mechanical corn sheller is found in 4 teeth, which is 45.81 kg / hour Keywords: Corn, Machine Sheller, Modifications, and Serration.